The Transformation of Traditional Islamic Education: Model of Modernization of Islamic Boarding Schools in Ogan Ilir - Muhammad Miqdar Maulidi; Fajri Ismail; Karoma Karoma; Mardeli Mardeli (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
This study aims to analyze the transformation of traditional Islamic education in Islamic boarding schools through the modernization model applied in Ogan Ilir Regency. The main problem raised is how the concept, characteristics, models, and modernization strategies are applied to Islamic boarding schools that were previously salafiyah and how these Islamic boarding schools respond to the challenges of the times in the field of education. The background of this research is based on the increasingly complex demands of the public on Islamic educational institutions to be able to adapt to the development of science, technology, and socio-cultural dynamics. The method used in this study is qualitative-descriptive with a case study approach. Data were collected through observation, in-depth interviews, and documentation studies of three Islamic boarding schools in Ogan Ilir: Al Ittifaqiah, Albasya, and Darul Funun. The findings of the study show that the modernization of pesantren education in Ogan Ilir includes curriculum reform, the adoption of classical systems, the strengthening of general education, and the use of information and communication technology. The strategy implemented involves integrating relevant old values with new, more adaptive innovations. The hybrid model between salaf and khalaf education is the dominant pattern in this transformation. The conclusion of this study emphasizes that modernization does not eliminate the identity of Islamic boarding schools, but rather strengthens their competitiveness in the midst of social change. Islamic boarding schools are able to become Islamic educational institutions that are responsive, adaptive, and relevant in the modern era.